Possible therapeutic effects of Nigella sativa and its thymoquinone on COVID-19 - Mohammad Reza Khazdair; Shoukouh Ghafari; Mahmood Sadeghi (Taylor & Francis Group, 2021)
Context COVID-19 is a novel coronavirus that causes a severe infection in the respiratory system. Nigella sativa L. (Ranunculaceae) is an annual flowering plant used traditionally as a natural food supplement and multipurpose medicinal agent. Objective The possible beneficial effects of N. sativa, and its constituent, thymoquinone (TQ) on COVID-19 were reviewed. Methods The key words including, COVID-19, N. sativa, thymoquinone, antiviral effects, anti-inflammatory and immunomodulatory effects in different databases such as Web of Science (ISI), PubMed, Scopus, and Google Scholar were searched from 1990 up to February 2021. Results The current literature review showed that N. sativa and TQ reduced the level of pro-inflammatory mediators including, IL-2, IL-4, IL-6, and IL-12, while enhancing IFN-γ. Nigella sativa and TQ increased the serum levels of IgG1 and IgG2a, and improved pulmonary function tests in restrictive respiratory disorders. Discussion and conclusions These preliminary data of molecular docking, animal, and clinical studies propose N. sativa and TQ might have beneficial effects on the treatment or control of COVID-19 due to antiviral, anti-inflammatory and immunomodulatory properties as well as bronchodilatory effects. The efficacy of N. sativa and TQ on infected patients with COVID-19 in randomize clinical trials will be suggested.